The Anatomical Position of Appendix in Iranian Cadavers - Tofighi, H; Taghadosi-nejad, F; Abbaspour, A; Behnoush, B; Salimi, A; Dabiran, S; Ghorbani, A; Okazi, A (International Journal of Medical Toxicology and Forensic Medicine, 2013)
Background: Vermiform appendix is different in terms of anatomical position, length and mesoappendix. Knowing the anatomical position of vermiform appendix is important for the surgeons in terms of diagnosis and management. The aim of this study is analysis of length, anatomical position and mesoappendix of vermiform appendix. Methods: This is a cross-sectional study on the 400 randomly selected cadavers (306 male and 94 female) who have been referred to the autopsy hall of legal medicine organization of Tehran province to be autopsied between March 21, 2010 and March, 2011. The cause of death was very heterogeneous among autopsied cadavers. Results:According to our results the anatomical positions were pelvic, subcecal, retroileal, retrocaecal, ectopic and preileal in 55.8%, 19%, 12.5%, 7%, 4.2% and 1.5% respectively. The mean length of vermiform appendix was 91.2 mm and 80.3 mm in men and women, respectively. Mesoappendix was complete in 79.5% and incomplete in 20.5%. No association was seen between sex and anatomical position of vermiform appendix. Conclusion:Anterior anatomical position was the most frequent vermiform appendix position in our population which is in discrepancy with most of the reports from western countries. It might be possible that factors such as race, geographical regions and nutritional regiment play roles in determining the position of vermiform appendix.